Study on rock mechanical properties of deep shale gas reservoirs based on multi-mechanical experiments - FENG Shaoke, XIONG Liang (Youqicang pingjia yu kaifa)
The southeastern Sichuan region is characterized by complex tectonic structures. The shale gas reservoir from the first member of the upper Ordovician Wufeng Formation to the Lower Silurian Longmaxi Formation is buried at considerable depths, which significantly affects the rock mechanical properties. However, systematic studies remain limited. This study focuses on the deep shale gas reservoir in the Lintanchang area of southeastern Sichuan. A series of mechanical experiments, including triaxial compressive tests, acoustic wave velocity measurements, tensile strength tests, and fracture toughness tests, were carried out. Based on the results of these multi-mechanical experiments, the rock mechanical properties of shale samples were analyzed, and a vertical mechanical property profile for a single well was established. With increasing temperature and pressure, the residual stress after fracture, Young’s modulus, and Poisson’s ratio of the deep shale samples showed an upward trend. The post-peak stress-strain curves exhibited more pronounced fluctuations. Acoustic wave velocities at the plunging end of the Lintanchang anticline were lower than those at the flanks. Young’s modulus and Poisson’s ratio values, corrected using a dynamic-static linear transformation, exhibited improved accuracy. The maximum load borne by the deep shale samples was less than 10 kN. Type Ⅰ and Type Ⅱ fractures displayed notable differences in propagation characteristics, and the degree of fracture penetration was greatly affected by sampling direction. The vertical mechanical profile of well T4 revealed that the bottom section of the first member of the Wufeng-Longmaxi Formation has higher Young’s modulus, lower Poisson’s ratio, and stronger brittleness, while the compressive and tensile strengths, as well as the fracture toughness index, remain relatively low. These mechanical properties show a weak compressive-tensile state, providing favorable conditions for reservoir stimulation. Thus, this interval represents an optimal target for future exploration and development.